Penerapan Model Pembelajaran Kolaboratif pada Mata Kuliah Komputasi Paralel dan Terdistribusi untuk Meningkatkan Keterampilan - Zulkipli, Zulkipli; Nulkamil, Putra Hasan; Risla, Syaif Al Feiqo; Adrian, M. Reza (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to examine the implementation of a collaborative learning model in the course of Parallel and Distributed Computing to enhance students' teamwork skills. The approach used is a case study with a qualitative method. Data were collected through observation, interviews, questionnaires, and document analysis, and then analyzed qualitatively and quantitatively. The results of the study show that the collaborative learning model significantly improves students' ability to interact, share responsibilities, and work towards common goals. This improvement has a positive impact on the output quality of the project and understanding of learning concepts. This research emphasizes the importance of integrating collaborative approaches into the Computer Engineering curriculum to prepare graduates to face complex and interdisciplinary challenges in the workforce.